THE EFFECT OF PERCEIVED EASE, TRUST, AND RISK PERCEPTION ON INTEREST IN USING THE DANA APPLICATION (Study On The Community Of Singkil District, Aceh Singkil Regency) - Winda; Halida Bahri; Muchsin; T. Edyansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine how the influence of the perception of convenience, trust, and risk perception on the interest in using the DANA Application in the community of Singkil District, Aceh Singkil Regency. The ease perception indicators used in this study consist of easy to use, easy to control, easy to understand, and flexible. Then the trust indicator consists of openness, fulfillment, loyalty, honesty, and trustworthiness. Meanwhile, the risk perception indicators used consist of financial risk, social risk, performance risk, time and convenience risk, physical risk, and psychological risk. As well as usage interest indicators consist of transactional interest, referential interest, preferential interest, and exploratory interest. The data used in this study was primary data obtained by distributing questionnaires to 115 people in Singkil District, Aceh Singkil Regency who used the DANA Application. The data analysis technique used in this study is multiple linear regression analysis using the help of SPSS software version 26. The results showed that the perception of ease and trust had a positive and significant effect on interest in use. Meanwhile, risk perception has a negative and significant effect on interest in using the DANA Application in the people of Singkil District, Aceh Singkil Regency.